ЕФЕКТИВНІСТЬ ЗАСТОСУВАННЯ МІКРОБНИХ ПРЕПАРАТІВ У СИСТЕМІ ЗАХИСТУ ХМЕЛЮ ВІД ЗБУДНИКІВ КОРЕНЕВИХ ГНИЛЕЙ - Венгер , В.М.; Якубенко , І.В.; Ільїнська , М.М.; Надкерничний , С.П. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2009)
The efficiency of new microbial preparations Chetomyk and Agat 25K use as remedies for hop protection against root rot agents was studied. It was established that treatment of hop main rhizome with suspension of these preparations promoted for considerable limitation of root rot development (disease spreading reduced in 1,7 times and the efficiency rate reduced in 2,2 times), diminution of spike-looking bines on 36,1-77,1 % as compared to control variant and essential reduction of hop plantations thinning.